Alur Proses Sarana Penjualan di PT. Pupuk Kujang Cikampek - Beni Nulhakim; Kusnadi Kusnadi; Wahyudin Wahyudin (Jurnal Ilmiah Wahana Pendidikan, 2021)
PT. Pupuk Kujang Cikampek is one of the chemical industries in Indonesia whose activities manage chemicals into a variety of products with the main product being urea fertilizer. In the distribution mechanism, PT. Kujang Cikampek fertilizer distinguishes urea fertilizer into subsidized urea fertilizer and non-subsidized urea fertilizer. The difference is in the use of urea fertilizer (for the food sector, plantations and industry) and applicable pricing. One of the factors that can support the smooth implementation of product distribution to consumers is established a sales system that regulates the process of distributing products to consumers. Urea fertilizer sales system PT. Pupuk Kujang Cikampek has an important role in distributing urea fertilizer to farmers because in it there are provisions that must be considered by companies and distributors. This is due to the problem of a lesser understanding of distributors to the rules of subsidized fertilizers. this causing deviations in the distribution of urea fertilizer to farmers. This problem can be controlled by PT. Pupuk Kujang cooperates with the government in monitoring the distribution of subsidized fertilizer and establishing strict rules and sanctions to be adhered to by both distributors and retailers. Thus the company can meet the needs of farmers in accordance with the company's goals while paying attention to the company's profits.